Recent Developments in Cell-Based Microscale Technologies and Their Potential Application in Personalised Medicine - Kijanka, Gregor; Burger, Robert; Dimov, Ivan K.; Padovani, Rima; Lawler, Karen; O'Kennedy, Richard; Ducrée, Jens (IntechOpen, 2011)
None